Atenção básica em saúde bucal em Goiás - Nascimento, Renata do (2016)
Introduction: from the creation and implementation of the National Oral Health Policy in 2004, there has been a noticeable increase in access to public dental care. However, there are still major challenges to improving access and quality to dental services. Objective: To describe the organization of basic dental care in Goiás in 2012. Methodology: this is a descriptive study that analyzed the secondary data extracted from external evaluation component of the bank's National Program for Improving Access and Primary Care Quality (PMAQ-AB), first cycle, between September and October 2012. The sample consisted of 540 oral health teams (eSB) that responded to the questionnaire PMAQ-AB, located in 174 municipalities and distributed in 17 health regions (RS). Results: among the eSB, 42% conducted the scheduling of the population on any given day and time; over 80% conducted all dental procedures; 96.6% said that there is reception to spontaneous demands; 54% reported that there is a Dental Speciality Center of reference for the routing of the population in need of such care. The highest percentages of eSB which claimed to have a reference CEO were in the RS Environs South (96.6%), Serra da Mesa (92.3%) and Southwest II (81%). No team of RS Northeast I and II Northeast had CEO to reference. In the RS Red River, 90.9% of eSB affirmed not have a CEO for reference, the same occurred in the RS Railway in which 85.2% of the teams have nowhere to refer patients in need of care in dental specialties. Final Considerations: The Oral Health Care Network of the state of Goiás is still incipient. The future challenge is the consolidation of a regionalized Oral Health Care Network, where primary care is the major focus of attention.